Fen-teknoloji-mühendislik-matematik entegrasyonunun (stem) 5. sınıf öğrencilerinin algı, tutum, kavramsal anlama ve bilimsel yaratıcılıklarına etkisi - Gülhan, Filiz (My University, 2016)
Bu araştırmada Fen-Teknoloji-Mühendislik-Matematik entegrasyonunun (STEM) ortaokul beşinci sınıf öğrencilerinin STEM alanlarıyla ilgili algılarına, STEM alanlarına karşı tutumlarına, fen alanındaki kavramsal anlamalarına ve bilimsel yaratıcılıklarına etkisinin incelenmesi amaçlanmıştır. Araştırmada gömülü deneysel karma yöntem kullanılmıştır. Yöntemin nicel boyutunda yarı deneysel desen, nitel boyutunda ise durum çalışması gerçekleştirilmiştir. Araştırmanın çalışma grubunu 2014-2015 yılında İstanbul’daki bir ortaokulda öğrenim gören iki 5. sınıfın öğrencileri oluşturmuştur. Kontrol grubunda 27, deney grubunda 28 öğrenci yer almıştır. Kontrol grubunda araştırma-sorgulamaya dayalı MEB Fen Bilimleri dersi tarafından önerilen ders kitabı işlenirken, deney grubunda ders kitabına ilave olarak araştırmacı tarafından geliştirilen STEM odaklı etkinlikler uygulanmıştır. Araştırmanın uygulama aşaması 12 hafta sürmüş ve 6 STEM odaklı etkinlik gerçekleştirilmiştir. Araştırmada ele alınan algı değişkeni için nicel yapıdaki “STEM Algı Testi” ve nitel yapıdaki “Mühendis kimdir?’ Sorusuna Ait Çizimler” adlı veri toplama araçları kullanılmıştır. Tutum değişkeni için nicel yapıdaki “STEM Tutum Testi” ve nitel yapıdaki “Öğrencilerin Meslek Tercihleri İle İlgili Sorular” adlı veri toplama araçları kullanılmıştır. Fen alanına yönelik kavramsal anlama değişkeni için “Kavramsal Anlama Soruları” kullanılmış, nicel ve nitel olarak incelenmiştir. Bilimsel yaratıcılık değişkeni için ise deney grubundan “Bilimsel Yaratıcılık Soruları”, “Öğrenci Günlükleri”, “Tasarım Kâğıtları”, “Fotoğraflar ve Sunum Videoları” ile süreç boyunca elde edilen dokümanlar; “Bilimsel Yaratıcılık Rubriği” ve “Tasarım (Ürün) Değerlendirme Rubriği” ile analiz edilmiştir. Yapılan nicel ve nitel analizler sonucunda bulgulara ulaşılmıştır. STEM etkinliklerinin 5. sınıf öğrencilerinin STEM alanlarıyla ilgili algılarına etkisinin genel olarak olumlu olduğu ve mühendislik mesleğine yönelik algılarının doğru yönde gelişim göstermesinde etkili olduğu; STEM alanlarına karşı tutumlarına etkisinin genel olarak olumlu olduğu ve STEM alanlarındaki meslekleri seçme isteklerini genel olarak arttırdığı; fen alanına yönelik kavramsal anlama düzeylerini geliştirmede olumlu etkiye sahip olduğu; bilimsel yaratıcılıklarına bireysel gelişim anlamında etkisinin sınırlı düzeyde olduğu, en üst yaratıcılık düzeyi olan yansıtıcı düşünme katmanının gelişiminde daha etkili olduğu sonuçlarına varılmıştır. Ulaşılan sonuçlardan yararlanılarak uygulayıcılara ve araştırmacılara yönelik önerilerde bulunulmuştur. Fen-Teknoloji-Mühendislik-Matematik entegrasyonu (STEM), ortaokul, 5. sınıf, algı, tutum, kavramsal anlama, bilimsel yaratıcılık

In this research, it is aimed to examine the effects of Science-Technology-Engineering-Mathematics (STEM) integration on secondary school fifth grade students’ perception and their attitude towards STEM fields, on their conceptual understanding in science and on their scientific creativity. In the research, it is used embedded experimental mixed method. It is executed quasi-experimental design within the quantitive aspect of the method, and case study within the qualitative aspect. The study group of the research consists of two different 5. grade students studying in a secondary school in Istanbul between the years of 2014-2015. 27 students took part in control group, and 28 in experimental group. While the textbook suggested by the Ministry of National Education Science Programme based on inquiry was used in control group, in experimental group in addition to the textbook, it was also performed some activities focused on STEM developped by the researcher. The run phase of the research took 12 weeks and 6 STEM based activities were fulfilled. For the variable of perception, dealt in the research, were used data collection tools called “Test of STEM Perception” which is in a quantitive structure, and “The Drawings Belonged to the Question of ‘The Engineer, who is he/ she?’” which is in a qualitative form. For the variable of attitude, were used data collection tools called “Test of STEM Attitude” which is in a quantitative structure, and “The Questions Related to Career Preference of Students” which is in a qualitative form. For the variable of conceptual understanding relevant to Science, it was put into use “The Questions of Conceptual Understanding”, and examined in both quantitive and qualitative way. Lastly, for the variable of scientific creativity, “Scientific Creativity Questions”, “Student Diaries”, “Design Papers”, “Photographes and Presentation Videos” along with all the other documents obtained throughout the process from the experimental group were analysed by means of “Scientific Creativity Rubric” and of “Design (Product) Evaluation Rubric”. In consequence of quantitive and qualitative analyses, it has been reached findings. The effect of STEM activities on 5. grade students’ perception about STEM fields is positive in general; it is also effective on that their perception towards to engineering career to get developped in the right direction; its effect on their attitude towards STEM fields is generally positive and mostly it increases their desire to choose a career among STEM fields; it has a positive effect on developing their level of conceptual understanding in science; its effect on their scientific creativity is limited in terms of personal development; instead, in the reflective thinking layer which is the highest level of creativity, it is more effective. Through the results obtained, it is given some suggestions for researchers and practitioners. Integration of Science-Technology-Engineering-Mathematics (STEM), secondary school, fifth grade, perception, attitude, conceptual understanding, scientific creativity.
Keywords: Eğitim ve öğretim(İlk); Fen bilgisi; Türkiye